Mixing Corrosion of CaCO3 in Natural Waters. Issue 3 (2011) - Hui, Qian; Peiyue, Li
Abstract : The methods of aqueous speciation calculation, pH calculation and the solubility (precipitability) calculation of CaCO3 were used to study the mixing corrosion of CaCO3 in natural waters. Mixing processes were done between two unsaturated (with CaCO3 ) solutions, two oversaturated solutions and between an unsaturated solution and an oversaturated solution, respectively. Results show that the mixing corrosion can be divided into two different levels: mixing corrosion in strict sense and mixing corrosion in broad sense. When mixing corrosion occurs, the HCO3 - concentration in one end member solution is usually higher than that in the other solution, and the Ca 2+ concentration in the former solution is also usually higher than that in the latter one.